Features of success attribution in English as a Second Language (ESL) among tertiary-level learners in Malaysia - Nurul Kamalia Yusuf; Melor Md Yunus; Mohamed Amin Embi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Attribution is a term used to represent an act of establishing a reason for an event. There are many features of attribution that the learners tend to point to their achievement. This study was conducted to examine one of the causal attribution dimensions which are the locus of control; internal and external. It aims at providing answers to the level of English as a Second Language (ESL) achievement among the tertiary level learners and the features of their success attributions. The research herein consisted of a set of questionnaires to obtain responses on ESL students’ achievement and their inclination when attributing the causes of their achievement. 236 students answered the questionnaire. Data were analysed after the reliability 0.870 of the instrument was gained. The descriptive statistics were used to address the research questions. The findings indicate that the majority of the students were moderate achievers and attributed their success to both external and internal factors. The inclination is seen towards the external locus. Both external and internal attributions were notably ascribed to achievement, particularly on the success in ESL and teacher which is an external factor played a noteworthy role in achievement. Understanding the levels and their attributes help to prepare academic performance and meaningful instructions in academic subjects taught in English.